Study of Seasonal Changes In the Composition of River Water - Yakubov Kutfidin, Abdullaev Mukhammadali, Juraev Sherali, Akramov Akhror (Research Parks Publishing LLC, 2023)
This article presents the results of a study of the water of the Naryn River at the point of Kyzylravot in the Namangan region of the Republic of Uzbekistan. The issues of the influence of seasonal factors on the pollution of the source water, as well as the problems of water purification methods are considered.